A Highly Stable Copper‐Based Catalyst for Clarifying the Catalytic Roles of Cu0 and Cu+ Species in Methanol Dehydrogenation. (16th January 2018) - Yang, Huanhuan; Chen, Yanyan; Cui, Xiaojing; Wang, Guofu; Cen, Youliang; Deng, Tiansheng; Yan, Wenjun; Gao, Jie; Zhu, Shanhui; Olsbye, Unni; Wang, Jianguo; Fan, Weibin
Abstract: Identification of the active copper species, and further illustration of the catalytic mechanism of Cu‐based catalysts is still a challenge because of the mobility and evolution of Cu 0 and Cu + species in the reaction process. Thus, an unprecedentedly stable Cu‐based catalyst was prepared by uniformly embedding Cu nanoparticles in a mesoporous silica shell allowing clarification of the catalytic roles of Cu 0 and Cu + in the dehydrogenation of methanol to methyl formate by combining isotope‐labeling experiment, in situ spectroscopy, and DFT calculations. It is shown that Cu 0 sites promote the cleavage of the O−H bond in methanol and of the C−H bond in the reaction intermediates CH3 O and H2 COOCH3 which is formed from CH3 O and HCHO, whereas Cu + sites cause rapid decomposition of formaldehyde generated on the Cu 0 sites into CO and H2 .